SAT0376 The incidence, prevalence and use of urate lowering agents in hong kong: a population study from 2006 to 2016. (12th June 2018) - Cheung, T.T.; Tsoi, M.F.; Chung, M.H.; Cheung, B.M.Y.; Lau, W.C.S.
Abstract : Background: The prevalence of gout has increased significantly over the past decade, espeically in developed countries and Oceanic populations. The estimated prevalence of gout in the US, Canada and European countries was 3%. Asian countries, except Taiwan, were considered to have a lower prevalence of gout due to differences in ethnicity and lifestyle. Since there are no recent epidemiological data on gout in Hong Kong, we conducted this population study to determine the incidence and prevalence of gout in Hong Kong as well as the utilisation of urate lowering agents among patients with gout. Objectives: To determine the incidence, prevalence of gout and use of urate lowering agents in Hong Kong Methods: Data were retrieved from the Clinical Data Analysis and Reporting System (CDARS) of the Hospital Authority. The Hospital Authority is the only public healthcare provider in Hong Kong. Since treatment is heavily subsidised and available to all residents, it covers more than 90% of all medical care for the general population in Hong Kong. Clinical data including demographic, diagnosis of gout, serum urate levels and prescriptions of urate lowering agents were retrieved from CDARS from 2006 to 2016. For inclusion, subjects must have attended any out-patient clinics or accident and emergency department (with or without hospitalisation) in 2005. Subjects with a diagnosis of gout who died before 2006 were excluded. All subjects were followed until the cut-off date or death. Gout was defined as the physician diagnosis and coding in CDARS. The serum urate levels achieved after prescribing urate lowering agents were the means of all serum urate levels 6 months after prescriptions. Results were analysed by R statistics version 3.3.3. with package 'prevalence' version 0.4.0. Results: 2741862 participants were included in the analysis. Both the incidence and prevalence of gout in Hong Kong have increased over the past 10 years. In 2016, the crude and age-standardised prevalence of gout were 2.92% and 1.44%, respectively. 6.26% of the general populaton aged 80 years or older was diagnosed to have gout. Despite the increase in incidence and prevalence of gout in Hong Kong, the utilisation of urate lowering agents remained low. in 2016, only 25.55% of patients with gout were prescribed urate lowering agents. More importantly, only 35.8% of those could achieve the therapeutic target of serum urate level <6 mg/dL. Conclusions: Population ageing has led to increases in incidence and prevalence of gout in Hong Kong. In 2016, the crude prevalence of gout in Hong Kong was 2.92%, which is similar to figures reported in western countries. Despite an increase in prevalence of gout, the utilisation of urate lowering agents remained low. Only 1 in 4 patients with gout were prescribed urate lowering agents. Acknowledgements: The Hospital Authority of Hong Kong Disclosure of Interest: None declared